Ribosome impairment regulates intestinal stem cell identity via ZAKɑ activation - Joana Silva; Ferhat Alkan; Sofia Ramalho; Goda Snieckute; Stefan Prekovic; Ana Krotenberg Garcia; Santiago Hernández-Pérez; Rob van der Kammen; Danielle Barnum; Liesbeth Hoekman; Maarten Altelaar; Wilbert Zwart; et al. (Nature Communications, 2022)
Intestinal stem cells are responsible for replenishing cells within the high-turnover intestinal epithelium. Here they show that ribosome dynamics affect intestinal stem cell identity through a mechanism that is triggered by changes in nutrient availability.